Value Creation and Firm Innovativeness of Small and Medium-Sized Enterprises in Ogun State, Nigeria - Akpa, V O; Shodunke, O O; Makinde , O G; Nwankwere, IA (Journal of Strategic Management, 2022)
Background: Small and medium-sized enterprises are globally viewed as an important force driving economic development and employment creation in both developing and developed countries, which is well acknowledged. However, the performance of SMEs in developed and developing economies has been slow and in some cases even collapsed due to a number of challenges such as the inability to respond to rapidly changing market demand, technical advancements, and capacity constraints related to knowledge, innovation and creativity all of which have negatively impacted on SMEs' performance leading to inability to sustain SMEs competitive advantage, decline in sales-growth, profitability and reduced innovative-capability. Extant studies have attempted to elucidate on the challenges of SMEs and the attendant supposed solutions, conversely, most of the extant research focus more on developed countries than developing countries such as Nigeria. Purpose: This study examined the effect of value creation on firm innovativeness of small and medium-sized enterprises in Ogun State, Nigeria. Methodology: The study adopted a survey research design. The population was 2,465 registered small and medium scale enterprises in Ogun State, Nigeria. A sample size of 432 was determined using Cochran formula. Proportionate stratified sampling technique was adopted. A validated questionnaire was used to collect data. Cronbach's alpha reliability coefficients for the constructs ranged from 0.79 to 0.92. The response rate was 87.9%. Data were analyzed using descriptive and inferential statistics. Findings: Findings revealed that value creation components had significant effect on innovativeness (Adj.R2 = 0.792; F (3,407) = 522.888, p < 0.05). The study concluded that value creation had a significant effect on firm innovativeness of SMEs in Ogun state, Nigeria. Recommendation: The study recommended that value creation components enhanced small and medium enterprises' innovativeness and therefore, owners/managers should continually create value in other to enhance SMEs innovativeness.